The Effectiveness of Water Treatment in the Wastewater Treatment Plant (WWTP) of the Tempe Industry and Benefits to the Community - Bayu Kartikasari, Ika; Butar-Butar, Binsar; Rachmi Indahsari, Siti; Adi Suhendra, Ahmad (International Journal of Science and Environment (IJSE), 2022)
The results of the tempe-making process will produce waste that is harmful to theenvironment from the washing, boiling, pressing and printing processes. The tempeindustry in Plaju ulu village is a source of community income. Tempe industryactivities produce waste that can pollute the environment, causing unpleasant odors.The wastewater treatment plant built by Pertamina RU 3 Plaju has a positive impactin reducing the impact of the tempe industry liquid waste. The formulation of theproblem raised (1) The results of the effectiveness of the Plaju Tempe IndustryWWTP. (2) Recommendations for WWTP technology that can be used in the PlajuTempe Industry. The parameters used to measure the quality of the effluent are pH(degree of acidity), COD, BOD, TSS, and (Total Suspended Solid) during July andAugust 2022. To determine the quality of wastewater produced, data fromlaboratory test results must be compared with quality standards. waste water inaccordance with the Regulation of the Minister of Environment of the Republic ofIndonesia No. 5 of 2014. From the results of the processing effectiveness, theeffectiveness of COD, BOD, and TSS was found to be 53.81%; 11.05%; and 22.65%.From the results of this processing, it is still considered not able to reduce thepollutants generated from the tempe industry activities. The pH and TSS parametersstill do not meet the quality standards. The recommended waste treatment isanaerobic biofiltration, anaerobic digester, and phytoremediation in improving theparameters of pH, COD, BOD, and TSS in the tempe-making industry